2016
DOI: 10.1016/j.jcf.2015.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Faecal proteomics: A tool to investigate dysbiosis and inflammation in patients with cystic fibrosis

Abstract: Faecal metaproteomics provides insights in intestinal dysbiosis, inflammation in patients with CF and can be used to monitor different disease markers in parallel.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 31 publications
5
75
0
Order By: Relevance
“…These results differ from the findings of a recent study that applied a metaproteomic approach to analyze CF fecal samples, and reported reduced proteins taxonomically attributed to butyrate-producing bacteria and increased proteins associated with R. gnavus and Clostridia species (Debyser et al. 2016). Further investigations are required to explain these discrepancies.…”
Section: Resultsmentioning
confidence: 99%
“…These results differ from the findings of a recent study that applied a metaproteomic approach to analyze CF fecal samples, and reported reduced proteins taxonomically attributed to butyrate-producing bacteria and increased proteins associated with R. gnavus and Clostridia species (Debyser et al. 2016). Further investigations are required to explain these discrepancies.…”
Section: Resultsmentioning
confidence: 99%
“…These metagenomic alterations correlated with both fecal fat content and measures of inflammation, suggesting that enteral lipid abundance may enrich for pro‐inflammatory microbiota in children with CF. This model is supported by observations from clinical trials of probiotics in CF patients, as will be discussed in more detail below, as well as from a study of bacterial and host proteins (i.e., using proteomics) in CF fecal samples …”
Section: Relationship Between Gi Microbiota and Cf Gi Diseasementioning
confidence: 61%
“…The microbiome, which is often called the 'forgotten organ', is essential for maintaining human health and physiology, but has now been associated with several diseases including cancer, IBD, coeliac disease, obesity, cardiac disease, psoriasis, asthma, autism, [33] CDI, and cystic fibrosis. [34] While earlier studies used mainly genomic-or transcriptomic-based approaches, faecal proteomics is now filling a new niche. [35] The initial non-targeted, shotgun MS/ MS-based metaproteomics study of the faecal microbiome used stool samples from two identical twins.…”
Section: The Faecal Microbiomementioning
confidence: 99%